Visual Colorimetric Detection of Edible Oil Freshness for Peroxides Based on Nanocellulose - Xiongli Jiang; Jun Cheng; Fangwei Yang; Zhenyang Hu; Zhen Zheng; Yu Deng; Buyuan Cao; Yunfei Xie (Foods, 2023)
Traditional methods for evaluating the edibility of lipids involve the use of organic reagents and complex operations, which limit their routine use. In this study, nanocellulose was prepared from bamboo, and a colorimetric reading strategy based on nanocellulose composite hydrogels was explored to monitor the freshness of edible oils. The hydrogels acted as carriers for peroxide dyes that changed color according to the freshness of the oil, and color information was digitized using UV-vis and RGB analysis. The sensitivity and accuracy of the hydrogel were verified using H2O2, which showed a linear relationship between absorbance and H2O2 content in the range of 0–0.5 and 0.5–11 mmol/kg with R2 of 0.9769 and 0.9899, respectively, while the chromatic parameter showed an exponential relationship with R2 of 0.9626. Surprisingly, the freshness of all seven edible oil samples was correctly identified by the hydrogel, with linear correlation coefficients greater than 0.95 in the UV-vis method and exponential correlation coefficients greater than 0.92 in the RGB method. Additionally, a peroxide value color card was established, with an accuracy rate of 91.67%. This functional hydrogel is expected to be used as a household-type oil freshness indicator to meet the needs of general consumers.